Pengembangangan Buku Ajar Berbasis Inkuiri Terbimbing pada Mata Pelajaran Otomatisasi Tata Kelola Humas dan Keprotokolan Kelas XII OTKP Semester Gasal di SMKN 10 Surabaya - Fitri Handayani; Durinta Puspasari (Universitas Negeri Surabaya, 2020)
This development research aims to describe the process of developing textbooks, analyze the feasibility of textbooks, and analyze students' responses to guided inquiry based textbooks on Automation and Public Relations and Protocol class XII OTKP odd semester. The development model used is a 4-D model that consists of four stages, namely defining, designing, developing, and disseminating. This research was conducted at SMKN 10 Surabaya. The subject of this research was class XII OTKP 3 consisting of 20 students as a limited trial. The validation results from experts showed that the feasibility of the material was 95%, the feasibility of the language was 88%, and the feasibility of the graphic was 82%. So that the overall average value of 88% with the interpretation criteria is very feasible. While the results of limited trials to determine student responses to textbooks developed by 96% with very interesting interpretation criteria. Thus, guided inquiry based textbooks on Automation and Public Relations and Protocol class XII OTKP in the odd semester were declared to be suitable as teaching materials.